Association of Sedentary Time and Physical Activity With Executive Function Among Children - Zeng, Xia; Cai, Li; Wong, Stephen Heung-sang; Lai, Lijuan; Lv, Yajie; Tan, Weiqing; Jing, Jin; Chen, Yajun (Academic pediatrics, 2021)
This study aimed to examine individual and combined associations between after-school sedentary time (ST) and daily physical activity (PA) with executive function development in children. The study included 4304 children aged 6 to 12 years. ST and PA were assessed using the International Physical Activity Questionnaire Short Form, and executive function was assessed using the Behavior Rating Inventory of Executive Function (Parent Version). Participants were classified as low (<2 h per day) or high (≥2 h per day) ST and low (not meeting guidelines) or high (meeting guidelines) PA. Resulting groups were defined as 1) low ST/high PA, 2) low ST/low PA, 3) high ST/high PA, and 4) high ST/low PA. Children in group 4 had the highest mean T-scores for BRIEF indices (48.23 ± 8.44, indicating increased symptoms of executive function dysfunction), followed by those in group 3 (47.10 ± 8.05), group 2 (45.81 ± 7.78), and group 1 (44.41 ± 7.31). ST was positively related to the T-score of all indices, independent of moderate-to-vigorous physical activity (MVPA). Significantly negative associations were observed between MVPA and Metacognition Index only in the high ST subgroup. Low ST and high PA were positively associated with executive function development in children. Notably, children with high ST and high PA demonstrated more significant deficits in executive function than those with low ST and low PA, suggesting that intervention efforts should focus on ST reduction in addition to promoting PA.